Galloyl-Hexahydroxydiphenoyl (HHDP)-Glucose Isolated From Punica granatum L. Leaves Protects Against Lipopolysaccharide (LPS)-Induced Acute Lung Injury in BALB/c Mice - Pinheiro, Aruanã Joaquim Matheus Costa Rodrigues; Mendes, Aleff Ricardo Santos; Neves, Milena Dara Farias de Jesus; Prado, Carla Máximo; Bittencourt-Mernak, Márcia Isabel; Santana, Fernanda Paula Roncon; Lago, João Henrique G.; de Sá, Joicy Cortez; da Rocha, Claudia Quintino; de Sousa, Eduardo Martins; Fontes, Valéria Costa; Grisoto, Marco Augusto Gregolin; et al. (Frontiers in Immunology, 2019)
The hydroalcoholic extract and ethyl acetate fraction of Punica granatum leaves have been known to exhibit anti-inflammatory activities. In this study, we investigated the therapeutic effects of galloyl-hexahydroxydiphenoyl (HHDP)-glucose isolated from pomegranate leaves on lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice. Male BALB/c mice were treated with different doses of galloyl-HHDP-glucose (5, 50 and 100mg/Kg) or dexamethasone at 5mg/Kg (per os) 6 h after intra-tracheal instillation of LPS. Vehicle-treated mice were used as controls. Twenty-four hours after LPS challenge, bronchoalveolar lavage fluid (BALF) and lung samples were collected for analyses. They were evaluated by monitoring the expression of NF-kB, JNK, and cytokine genes and proteins, as well as cell migration and lung function. All doses of galloyl-HHDP-glucose inhibited LPS-induced JNK and NF-kB activation. Likewise, the galloyl-HHDP-glucose-treated animals presented reduced expression of the TNF-α, IL-6, and IL-1β genes in the lungs and reduced TNF-α, IL-6, IL-1β, and IL-8 protein levels when compared with the vehicle-treated LPS-challenged mice. In addition, the ALI mice treated with galloyl-HHDP-glucose also presented reduced lung inflammatory cell accumulation, especially that of neutrophils, in their BALF and lungs. In addition, galloyl-HHDP-glucose treatment markedly ameliorated the LPS-induced pulmonary mechanism complications and attenuated weight loss. Overall, we showed for the first time that galloyl-HHDP-glucose protects against ALI, and may be useful for treating ALI and other inflammatory disorders.